2021
DOI: 10.1002/edn3.256
|View full text |Cite
|
Sign up to set email alerts
|

Creating genetic reference datasets: Indirect sampling of target species using terrestrial leeches as sample “collectors”

Abstract: Sampling genetic material from rare and often secretive mammals can be difficult in challenging environments such as tropical rainforests. Large-scale sampling is important however for resolving species' taxonomic uncertainties, as well as to help provide genetic material for reference databases that can be used with DNA forensics to combat the illegal wildlife trade. Environmental DNA (eDNA) and invertebrate-derived DNA (iDNA) offer a promising way to overcome this sampling bottleneck, though to date e/iDNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…However, to rely on cameras implies the risk of losing data (over 40 days, 1/14 cameras were lost) and demands repeated visits which may be complicated in remote areas (at least installation and recovery of cameras), where eDNA sampling offers valuable study opportunities (McInnes et al, 2021). Also, CT does not offer the same options as eDNA in terms of possible population genetic studies (Bohmann et al, 2018; Nguyen et al, 2021; Sigsgaard et al, 2016, 2020; Tilker et al, 2020; Wilting et al, 2021) and the extension to other phyla (as, e.g., invertebrates, plants, and bacteria). eDNA sampling is appealing due to its sensitivity, standardization, and non‐invasiveness, as well as the independence from taxonomic experts for taxa identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to rely on cameras implies the risk of losing data (over 40 days, 1/14 cameras were lost) and demands repeated visits which may be complicated in remote areas (at least installation and recovery of cameras), where eDNA sampling offers valuable study opportunities (McInnes et al, 2021). Also, CT does not offer the same options as eDNA in terms of possible population genetic studies (Bohmann et al, 2018; Nguyen et al, 2021; Sigsgaard et al, 2016, 2020; Tilker et al, 2020; Wilting et al, 2021) and the extension to other phyla (as, e.g., invertebrates, plants, and bacteria). eDNA sampling is appealing due to its sensitivity, standardization, and non‐invasiveness, as well as the independence from taxonomic experts for taxa identification.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental DNA from terrestrial animals has been mostly assessed by analyzing scats (De Barba et al, 2014; Kartzinel et al, 2015; Swift et al, 2018), soil (Leempoel et al, 2020; Yoccoz et al, 2012; Zinger et al, 2019), stomach content samples (Kennedy et al, 2019; Masonick et al, 2019; Soininen et al, 2013), leeches blood meals (Abrams et al, 2019; Nguyen et al, 2021; Tilker et al, 2020; Weiskopf et al, 2018; Wilting et al, 2021), or carrion flies (Calvignac‐Spencer et al, 2013; Gogarten et al, 2020; Rodgers et al, 2017; Schubert et al, 2015). Bulk tissue samples (mixtures of, e.g., insects or other macroinvertebrate specimens) are also increasingly used not only to assess invertebrate diversity but also as an indirect way to sample vertebrate DNA (Lynggaard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These arthropods have been limited to hematophagous insects such as mosquitoes, ticks, blackflies, triatomine bugs, and sandflies. In recent years, the extension from vectors to other invertebrates such as leeches (Alfano et al, 2021; Schnell et al, 2012; Wilting et al, 2021) and flies (Calvignac‐Spencer et al, 2013) and the development of the metabarcoding protocol have enabled the sampling of vertebrates through invertebrate samples beyond the scope of disease transmission. This resulted in the development of invertebrate‐derived DNA (iDNA) within the umbrella of environmental DNA and its use as monitoring tool, also for rare and elusive species (Nguyen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible to obtain DNA from reptile faeces to conduct monitoring and analysis [65][66][67], this is usually dependent on the collection of fresh samples [65]. Additionally, iDNA degrades quickly within the digestive tract of invertebrates [27,68]. It is worth noting that despite attempts to detect various different classes of animals, overall detection was poor throughout the study, and no significant differences in detection were observed between taxonomic classes.…”
Section: Detection Of Different Animal Taxamentioning
confidence: 99%